Monitoring training to assess changes in fitness and fatigue: The effects of training in heat and hypoxia. (June 2015) - Crowcroft, S.; Duffield, R.; McCleave, E.; Slattery, K.; Wallace, L. K.; Coutts, A. J.
Abstract : This study examined the association between monitoring tools, training loads, and performance in concurrent heat and hypoxia (H + H) compared with temperate training environments. A randomized parallel matched‐group design involved 18 well‐trained male cyclists. Participants performed 12 interval sessions (3 weeks) in either H + H (32 ± 1 °C, 50% RH, 16.6% O2 normobaric hypoxia) or control (21 °C, 50% RH, 21% O2 ), followed by a seven‐session taper (3 weeks; 21 °C, 50% RH, 21% O2 ), while also maintaining external training (∼ 6–10 h/week). A 20‐km time trial (TT) was completed pre‐ and post‐training block (21 °C, 50% RH, 21% O2 ). Before each TT and once weekly, a 4‐min cycle warm‐up (70% 4‐min mean maximum power) was completed. Visual analog scale rating for pain, recovery, and fatigue was recorded before the warm‐up, with heart rate (HREx ), heart rate recovery (HRR), and rating of perceived exertion (RPEWU ) recorded following. Training load was quantified using the session rating of perceived exertion (sRPE) method throughout. Overall TT improved 35 ± 47 s with moderate correlations to HRR ( r = 0.49) and recovery ( r = −0.55). H + H group had a likely greater reduction in HREx [ES = −0.50 (90% CL) (−0.88; 0.12)] throughout and a greater sRPE (ES = 1.20 [0.41; 1.99]), and reduction in HRR [ES = −0.37 (−0.70;−0.04)] through the overload. RPEWU was associated with weekly training load ( r = 0.37). These findings suggest that recovery and HRR in a temperate environment may be used as simple measures to identify an athlete's readiness to perform. Alternatively, the relationship of RPEWU and training load suggests that perception of effort following a standardized warm‐up may be a valid measure when monitoring an athlete's training response, irrespective of the training environment.